Efficacy and safety of the pars plana clip in the Ahmed valve device inserted via the pars plana in patients with refractory glaucoma - Manuel Diaz-Llopis (Dove Medical Press, 2010)
Manuel Diaz-Llopis1,2,3, David Salom1,3, Salvador García-Delpech1,2,3, Patricia Udaondo1,3, Jose Maria Millan3,5, J Fernando Arevalo61Department of Ophthalmology, La Fe University Hospital of Valencia, Valencia, Spain; 2Department of Ophthalmology of the Valencia University, Valencia, Spain; 3Biomedical Network Research Centre on Rare Diseases (CIBERER), Valencia, Spain; 4Catholic University San Vicente Martir, Valencia, Spain; 5Department of Genetics, La Fe University Hospital of Valencia, Valencia, Spain; 6Clinica Oftalmologica Centro Caracas, Retina and VItreous Service, Caracas, DC, VenezuelaPurpose: To evaluate the efficacy and safety of the pars plana clip (PPC) in the Ahmed valve tube inserted via the pars plana in patients with secondary refractory glaucomas.Methods: Prospective and interventional case series that included 10 patients with secondary refractory glaucoma. The pars plana vitrectomy and the implant of the modified tube were performed during the same surgery. Control of intraocular pressure (IOP) and the development of intra- and postoperative complications were evaluated during the follow-up.Results: Follow-up time was twelve months in all the patients. Control of IOP was achieved in 90% of patients, and 70% needed no antiglaucoma treatment. The complications that occurred were transient hypotony in three cases, choroidal detachment in two cases, and one case of intraocular hemorrhage. No case of tube extrusion or tube kink was observed.Conclusions: Our data suggests that implantation of the Ahmed tube modified with the PPC via the pars plana is safe and effective in patients with secondary refractory glaucomas. Keywords: pars plana clip, Ahmed valve, refractory glaucoma, pars plana vitrectomy